Customer purchase intention on skin care products / Valerie Diane Victor - Victor, Valerie Diane (2016)
The purpose of this study is to identify factors influencing customer purchase intention on skin care products. The problem statement of this research is people todays are relying on other woman's opinions which they heard through word of mouth and people tend to buy cheaper skin care products to get flawless face. There are three independent variables including customer trust, promotion and social media. In terms of data collection, sets of questionnaire are distributed using electronic survey. Therefore, the limitation of study includes cost constrain and respondent commitment in answering all the questions. This study is referring to Malhotra 2007 and this study is descriptive analysis which is quantitative data analysis. This research conducted in Kota Kinabalu area and focused on publics. The samples of this study is 200. The overall results of this study found that amongst all the independent variables, customer trust is the most significant. Last but not least, for future research should also be identify other factors such as service delivery of products, past experience and others.